Multicultural Dimension in Haq Naqsyabandi Thariqah - Muh. Gitosaroso; Sofwan; Nawawi Nawawi; Elmansyah Elmansyah (International Journal of Social Science and Religion (IJSSR), 2023)
History proves that Islam spread throughout the archipelago when the Hindu-Buddhist kingdom was still in power due to the work of da'I, who were members of certain tariqas. The principle of tolerance of the adherents of thariqah succeeded in attracting the interest of the people of the archipelago to the teachings of Islam, and they converted to Islam. It is interesting to investigate the multicultural dimension of thariqah further so that it can be used to describe the teachings of tarekat concerning Islamic proselytization in a multicultural society. Therefore, this research aims to reveal the multicultural dimension in the teachings of the Haq NaqsyabandiThariqah. The research is conducted with a philosophical approach to the teachings of thariqah, which is critically described through historical data and the most important manuscripts of thariqah. The research shows that every sect of thariqah has a teaching of tolerance in a multicultural society.